A Prospective Obsevational Study On Adnexal Masses -Comparison Of Clinical Impression, Ca -125, Ultrasound Findings And Histopathological Diagnosis - Salam, Soheli; Naz, Mahjabeen; Akter, Marufa (East West Medical College Journal, 2025)
Adnexal mass may be found in women of all ages with a prevalence of 1:1000 in premenopausal group and 3:1000 in post menopausal group. The risk of malignancy increases with age. The current study was carried out in the department of Obstetrics and Gynaecology in Ad-din Women’s Medical College Hospital, Maghbazar, Dhaka from Ist July 2023 to 30 th June 2024. It was a hospital based observational study which included 100 patients of adnexal masses who required surgery. The goal of the study was to compare sensitivity , specificity , predictive value of clinical evaluation , USG with colour Doppler, CA-125 ,RMI score and to compare them with histopatholoy. All cases were evaluated clinically, by Ultrasonogram with colour doppler ,CA-125 and RMI score. After surgery specimens were sent for histopathology and reports were compared with pre surgical evaluation. 93% cases were of ovarian origin and 7% were non ovarian cases. Histopathology reports showed that 68% adnexal masses were benign and 32% were malignant. The principle tool for evaluation of adnexal mass was Ultrasonogram with colour doppler which had the highest diagnostic accuracy(92%) . But clinical evaluation had the highest sensitivity(90.62%) and RMI score had the highest specificity(95.59%) .With these comparatively simple methods we can diagnose adnexal masses without expensive advanced imaging modalities. EWMCJ Vol. 13, No. 2, July 2025: 143-148